An innovative strategy in community development through corporate social responsibility: practices and outcomes - Alias, Siti Noormi; Ismail, Maimunah; Mohd. Rasdi, Roziah (2011)
Corporate social responsibility (CSR) is an innovative strategy in developing community resources in Malaysia. This article reports on results of a study on CSR practices and outcomes. The practices are examined based on orientations of the CSR implemented by corporations in community development particularly on living standards, education, and health of the community. These community development components are adopted from the Human Development Report (HDR) indices. CSR orientations are defined by adopting Carroll‘s (1991) conceptualization of CSR, which includes economic, legal, ethical and philanthropic responsibilities. The outcomes are examined through relationships between the CSR orientations and community development components. A structured 7-likert scale questionnaire was used to gather data from 204 respondents. The data showed significant positive relationship between CSR orientations with the living standards and education of the sample. The results also show significant positive relationship between legal and philanthropic CSR orientations with respondents‘ health component. The legal responsibility becomes the utmost priority, followed by the philanthropic, economic and ethical responsibility. Implications to CSR practices and research are put forth.